Rain-Call Dialects of the Chaffinch, Fringilla coelebs (Fringillidae), in Ukraine - Tsvelykh, A.N.; Yablonovska-Grishchenko, E.D. (Вестник зоологии, 2013)
Four types of Chaffinch rain-calls were found in Ukraine: “rulsch” – a trill signal widely spread in Europe; “hui” – a whistle signal that occurs in North-Western and Central Europe; “Crimean” whistle signal known only from Crimean peninsula and “Caucasian” signal occurring in Caucasus, Asia Minor and Balkans.